2013
DOI: 10.21608/jacb.2013.53208
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Cytoplasmic Male Sterile (Cms) and Restorer Lines in the Developing of Hybrid Rice.

Abstract: The present investigation was conducted to determine the magnitudes of combining ability and heterosis obtained from hybrids three produced by utilization of CMS, maintainer and restorer lines in rice. The experiment was carried out during the two growing seasons of 2010 and 2011 at Rice Research and Training Center (RRTC) Farm, Sakha, Kafr El-Sheikh, Egypt. Twelve F1 hybrids were obtained from crossing three CMS lines as female parent with four restorer lines. These hybrids were evaluated along with their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
8
2
0
Order By: Relevance
“…The contribution of line × tester interaction was important for spikelet fertility % (59.12%) only. These results are in agreement with those obtained by Abd El-Hadi et al (2013) and Hasan et al (2015).…”
Section: Estimates Of Genetic Parameterssupporting
confidence: 94%
See 4 more Smart Citations
“…The contribution of line × tester interaction was important for spikelet fertility % (59.12%) only. These results are in agreement with those obtained by Abd El-Hadi et al (2013) and Hasan et al (2015).…”
Section: Estimates Of Genetic Parameterssupporting
confidence: 94%
“…The results revealed that the dominance genetic variance (σ 2 D) was greater than the additive genetic variance (σ 2 A) in controlled the inheritance of all the studied traits, except days to heading, plant height and panicle weight which was governed by the additive genetic variance. These results are in accordance with those of Abd El-Hadi et al (2013) and Anis (2013). Heritability estimates in broad sense (h 2 b %) were high for all the studied traits.…”
Section: Estimates Of Genetic Parameterssupporting
confidence: 93%
See 3 more Smart Citations